hPG80 (circulating progastrin) as a blood biomarker for high-grade glial tumors: A pilot study - Casile, Melanie; Passildas, Judith; Vire, Bérengère; Molnar, Ioana; Durando, Xavier (Frontiers in Neurology, 2023)
Background Currently, the long-term prognosis and survival rate of patients with high-grade glial tumors remains poor and there are no biomarkers. hPG80 (circulating progastrin) secreted into the blood by tumor cells has been widely studied in colorectal cancer. Its involvement in tumorigenesis has been demonstrated in the literature. Moreover, according to a recent study, hPG80 is expressed in the blood of cancer patients at a significantly higher concentration than in the control group composed of healthy blood donors. Methods The PROGLIO study is a pilot, single-center, longitudinal study that primarily seeks to evaluate circulating plasma hPG80 concentrations over time in patients with high-grade glial tumors. A fasting blood sample will be taken on the start and end day of radiotherapy and during the adjuvant chemotherapy (every 3 cycles). Follow-up monitoring will be performed for 9 months, with a blood sample taken every 3 months on the day of the follow-up MRI. The study plans to recruit 30 patients and recruitment started in February 2022. Trial registration ClinicalTrials.gov, ID NCT05157594; registered on October 27, 2021.